Intrinsic challenges in x-ray spectrometry instrumentation with CdTe diode detector (Brazilian Journal of Radiation Sciences, 2021)
The X-ray spectrometry is subject to a diversity of problems that distort the measured beam. To observe them, spectra from N20, N25, N30, N60, N80, and N100 radiation qualities were obtained and evaluated their non-correction impact in the values of mean energy when compared with the requirements on ISO 4037-1 standard. The error percentages calculated were 2%, 2%, 2%, 11%, 9%, and 6%, respectively, related to partial energy deposition, efficiency loss, and charge trapping. These results suggest the need for correction of measured spectra, mainly for voltages higher than 30 kV.